Producción misionera sobre la lingüística chiriguana: Una mirada diacrónica - Morando, María Agustina (2018)
With the arrival of the European explorers to Americaa long tradition of missionary linguistic tools recorded thediverse particularities of indigenous languages. This resulted inthe preparation of dictionaries, grammars, lexicons, and phrasescompendia collecting various types of linguistic data of non-literatesocieties. Like many other Amerindian languages, the documentationof the Tupi-Guarani languages started with the worksof Jesuit and Franciscan missionaries as early as the beginning ofthe 16th century. Therefore, the aim of this article is to approachmissionary linguistic works concerning the Guarani linguistic varietyspoken in the Western Chaco from the 17th century to thepresent. The historiographical description and analysis are basedon a textual corpus consisting of works by various authors whoaddress the same linguistic variety in different historical periods.The geographical and temporal range of each text, the thematicand historiographical treatment and the production context aretaken into account in order to analyse these linguistic documents.The analyses of this linguistic corpus will allow us to accountfor the diachronic development of this Guarani variety that underwenta specific process of gramatization and dictionarization.This shed light on the activities of linguistic description as a constructionprocess that adopts multiple modalities and helps us tounderstand the standardization process of indigenous languagesystems.